Gaze-driven recording of video - Noorkami, Maneli; Desai, Ranjit (2023)
Systems and methods for gaze-driven recording of video are described. Some implementations may include accessing gaze data captured using one or more gaze-tracking sensors; applying a temporal filter to the gaze data to obtain a smoothed gaze estimate; determining a region of interest based on the smoothed gaze estimate, wherein the region of interest identifies a subset of a field of view; accessing a frame of video; recording a portion of the frame associated with the region of interest as an enhanced frame of video, wherein the portion of the frame corresponds to a smaller field of view than the frame; and storing, transmitting, or displaying the enhanced frame of video.